2022
DOI: 10.1002/smll.202202410
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Structure–Activity Relations in Proton Electroreduction at Pd Surfaces: Theoretical and Experimental Study

Abstract: The structure–activity relationship is a cornerstone topic in catalysis, which lays the foundation for the design and functionalization of catalytic materials. Of particular interest is the catalysis of the hydrogen evolution reaction (HER) by palladium (Pd), which is envisioned to play a major role in realizing a hydrogen‐based economy. Interestingly, experimentalists observed excess heat generation in such systems, which became known as the debated “cold fusion” phenomenon. Despite the considerable attention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 96 publications
0
12
0
Order By: Relevance
“…38 Schmidt et al have also recently shown that expansion of the Pd lattice leads to weaker adsorption energy of adsorbed H, enhancing the hydrogen evolution reaction rate in acidic medium. 39 ■ CONCLUSIONS In summary, our results shed fundamental light on the loss of H sorption capacity of Pd/C nanoparticles during repeated H insertion/de-insertion cycles. By combining electrochemistry and wide-angle X-ray scattering, we demonstrated that H atoms get progressively trapped in the Pd lattice.…”
Section: ■ Results and Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…38 Schmidt et al have also recently shown that expansion of the Pd lattice leads to weaker adsorption energy of adsorbed H, enhancing the hydrogen evolution reaction rate in acidic medium. 39 ■ CONCLUSIONS In summary, our results shed fundamental light on the loss of H sorption capacity of Pd/C nanoparticles during repeated H insertion/de-insertion cycles. By combining electrochemistry and wide-angle X-ray scattering, we demonstrated that H atoms get progressively trapped in the Pd lattice.…”
Section: ■ Results and Discussionmentioning
confidence: 73%
“…For example, PdH 0.43 NPs were shown to be more active for methanol oxidation reaction compared to the pure metal Pd counterparts . Schmidt et al have also recently shown that expansion of the Pd lattice leads to weaker adsorption energy of adsorbed H, enhancing the hydrogen evolution reaction rate in acidic medium …”
Section: Resultsmentioning
confidence: 99%
“…A lower amplitude and a larger full width at half maximum in OER ‘On’ than in OER ‘Off’ correspond to a higher distribution of derivative slopes and, therefore, to a higher activity. A more detailed explanation of this evaluation technique is available in the Methods Section and in references [ 49 ] and [ 53 ] . A white square in Figure S7a in the Supporting Information highlights the position of the evaluated area.…”
Section: Resultsmentioning
confidence: 99%
“…EIS and RDE techniques were performed using a VSP-300 potentiostat (Bio-Logic, France). Since the EIS measurements were performed at high frequencies, measurement artifacts caused by the impedance of the RE were suppressed by a shunt capacitor placed between the RE and a Pt wire, which was immersed into the electrolyte close to the Luggin capillary [27,33]. This is also how to make the iR compensation for the HER/HOR polarization curves.…”
Section: Methodsmentioning
confidence: 99%
“…[22][23][24][25][26]). Finally, we used Pd nanoparticles supported on high surface area carbon (Pd/C) as a promising hydrogen evolution electrocatalyst to demonstrate the informative power of the EIS-RDE approach for a more complex system [27,28]. To harvest results with profound physical meaning, a suitable equivalent electric circuit (EEC) model for the EIS data is used in this work [19].…”
Section: Introductionmentioning
confidence: 99%